Thymoquinone’s Antiviral Effects: It is Time to be Proven in the Covid-19 Pandemic Era and its Omicron Variant Surge - Abdelrahim, Maen; Esmail, Abdullah; Al Saadi, Noor; Zsigmond, Eva; Al Najjar, Ebtesam; Bugazia, Doaa; Al-Rawi, Hadeel; Alsaadi, Ayat; Kaseb, Ahmed O. (Frontiers in Pharmacology, 2022)
The COVID-19 pandemic has impacted every country in the world. With more than 290 million cases and more than 5 million deaths. The FDA either approved or authorized the emergency use for three vaccines against COVID-19. The treatment options of COVID-19 are very limited. There are multiple complementary and alternative medicine modalities that were suggested to be efficacious in the treatment of COVID-19 such as Thymoquinone. The effects of Thymoquinone have been examined and multiple studies indicate a promising beneficial effect. However, the current body of research is limited in terms of its scope, quality, and quantity. While higher-quality studies are required, physicians do not routinely recommend the use of marketed supplements of natural products, including Thymoquinone for COVID-19. Given the numerous suggested positive effects of Thymoquinone, including anti-inflammatory and antimicrobial properties, additional research is required to confirm or refute these promising benefits. Complementary and alternative medicine is an area that requires additional evidence-based practice and research to confirm effects observed in clinical practice.